Non-Lethal Farce: "Pepper Spray Cop" Photoshopping as Visual Rhetoric - Peck, Andrew M (AoIR Selected Papers of Internet Research, 2013)
This paper examines photoshopping as an important emerging genre of vernacular civic discourse on the Internet. By sharing digitally altered images (“photoshops”) across networks, users engage in a vernacular process that creates and participates in discourses concerning social knowledge, shared expectations, and shared values. To demonstrate this process, this paper analyzes how photoshopping was used as a response to the pepper spraying of a group of peaceful protesters on the University of California, Davis campus. Enabled by the affordances of networked communication, this paper argues that photoshopping represents a powerful new form of vernacular rhetoric for the digital age.